Proceedings of the 28th International Conference on Computational Linguistics 2020
DOI: 10.18653/v1/2020.coling-main.605
|View full text |Cite
|
Sign up to set email alerts
|

Do Neural Language Models Overcome Reporting Bias?

Abstract: Mining commonsense knowledge from corpora suffers from reporting bias, over-representing the rare at the expense of the trivial (Gordon and Van Durme, 2013). We study to what extent pre-trained language models overcome this issue. We find that while their generalization capacity allows them to better estimate the plausibility of frequent but unspoken of actions, outcomes, and properties, they also tend to overestimate that of the very rare, amplifying the bias that already exists in their training corpus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…Studying inconsistencies of PLM-KBs can also teach us about the organization of knowledge in the model, or lack thereof. Finally, failure to behave consistently may point to other representational issues such as the similarity between antonyms and synonyms (Nguyen et al, 2016), and overestimating events and actions (reporting bias) (Shwartz and Choi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studying inconsistencies of PLM-KBs can also teach us about the organization of knowledge in the model, or lack thereof. Finally, failure to behave consistently may point to other representational issues such as the similarity between antonyms and synonyms (Nguyen et al, 2016), and overestimating events and actions (reporting bias) (Shwartz and Choi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, previous research into LMs as knowledge bases has not been able to fully explore the extent to which they know color (A. Rodriguez and Merlo, 2020;Shwartz and Choi, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Gordon and Van Durme (2013) perform a quantitative analysis using n-gram frequencies from text, finding this phenomenon particularly relevant to internet text corpora. Shwartz and Choi (2020) extend these experiments to pretrained models such as Bert (Devlin et al, 2019) and RoBERTa (Liu et al, 2019). Similar to our work, they analyze color attribution of the form "The banana is tasty."…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have demonstrated that such bias is often manifested in pretrained language models [Sun et al, 2019]. These models further tend to exaggerate patterns of stereotypes in the underlying training data and thus amplify existing biases [Zhao et al, 2017;Shwartz and Choi, 2020]. This is particularly problematic if they are used as a starting point for other models, which likely adopt the biases.…”
Section: Introductionmentioning
confidence: 99%